Are Pressure Time Integral and Cumulative Plantar Stress Related to First Metatarsophalangeal Joint Pain? Results From a Community‐Based Study. Issue 9 (27th July 2016) - Rao, Smita; Douglas Gross, K.; Niu, Jingbo; Nevitt, Michael C.; Lewis, Cora E.; Torner, James C.; Hietpas, Jean; Felson, David; Hillstrom, Howard J.
Abstract : Objective: To examine the relationship between plantar stress over a step, cumulative plantar stress over a day, and first metatarsophalangeal (MTP) joint pain among older adults. Methods: Plantar stress and first MTP pain were assessed within the Multicenter Osteoarthritis Study. All included participants were asked if they had pain, aching, or stiffness at the first MTP joint on most days for the past 30 days. Pressure time integral (PTI) was quantified as participants walked on a pedobarograph, and mean steps per day were obtained using an accelerometer. Cumulative plantar stress was calculated as the product of regional PTI and mean steps per day. Quintiles of hallucal and second metatarsal PTI and cumulative plantar stress were generated. The relationship between predictors and the odds ratio of first MTP pain was assessed using a logistic regression model. Results: Feet in the quintile with the lowest hallux PTI had 2.14 times increased odds of first MTP pain (95% confidence interval [95% CI] 1.42–3.25, P < 0.01). Feet in the quintile with the lowest second metatarsal PTI had 1.50 times increased odds of first MTP pain (95% CI 1.01–2.23, P = 0.042). Cumulative plantar stress was unassociated with first MTP pain. Conclusion: Lower PTI was modestly associated with increased prevalence of frequent first MTP pain at both the hallux and second metatarsal. Lower plantar loading may indicate the presence of an antalgic gait strategy and may reflect an attempt at pain avoidance. The lack of association with cumulative plantar stress may suggest that patients do not limit their walking as a pain‐avoidance mechanism.